Relación entre el consumo de alcohol y la percepción social que se tiene sobre la violencia sexual hacia las mujeres en municipios del norte del Valle del Cauca. (2024)
This research is framed in the purpose of knowing the relationship between alcohol consumption and the social perception of sexual violence against women. The theoretical framework adressed includes gender-based violence, psychosocial factors and alcohol consumption. Qualitative research was implemented as the methodology since it collects the narratives, opinions and beliefs about the events of sexual violence against women who are found in contexts where alcohol is consumed. The information was obtained through the application of a semi-structured interview; the answers indicated that although violence should not be justified under any circumstances, there is usually criticism and even recrimination towards the victims of these events when, due to their clothing, proximity or alcohol consumption, they are responsible for promoting this type of abuse.